Cover. (19th April 2018) - Fricke, Erin M.; Elgin, Timothy G.; Gong, Huiyu; Reese, Jeff; Gibson‐Corley, Katherine N.; Weiss, Robert M.; Zimmerman, Kathy; Bowdler, Noelle C.; Kalantera, Karen M.; Mills, David A.; Underwood, Mark A.; McElroy, Steven J.
Abstract : Front cover : The cover image, by Erin M. Fricke et al., is based on the Original Article LPS‐induced maternal inflammation induces direct placental injury without alteration in placental blood flow and induces a secondary fetal intestinal injury that persists into adulthood, DOI10.1111/aji.12816